2022
DOI: 10.33043/sswj.1.1.136-162
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Violence Prevention Among Intercollegiate Athletes, Recreational Athletes, and Non-Athletes: Environmental Considerations for Program Interventions

Abstract: Previous research has suggested that individual, social, and environmental factors all play a role in developing individual attitudes regarding sexual violence. On college campuses, both intercollegiate and recreational athletics provide opportunities for students to engage in group settings that can impact these attitudes. The primary purpose of this study was to examine how attitudes towards sexual violence compared across intercollegiate athlete, recreational athlete, and non-athlete populations, while acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 65 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…Studies that have included the recreational population found that recreational athletes are more like “athletes” than “non-athletes.” Young et al (2017) compared SV risk factors between intercollegiate and recreational athletes, finding no significant differences between the two groups. Evans et al (2022) found recreational athletes were similar to intercollegiate athletes in terms of their attitudes toward SV, including personal and social norms and bystander efficacy. Considering these findings, and the potential for some recreational sport atmospheres to create an increased risk of SV violence (e.g., loyalty to teammates, competitiveness), it is important to treat recreational athletes as a distinct campus subgroup.…”
Section: Theoretical Frameworkmentioning
confidence: 75%
See 4 more Smart Citations
“…Studies that have included the recreational population found that recreational athletes are more like “athletes” than “non-athletes.” Young et al (2017) compared SV risk factors between intercollegiate and recreational athletes, finding no significant differences between the two groups. Evans et al (2022) found recreational athletes were similar to intercollegiate athletes in terms of their attitudes toward SV, including personal and social norms and bystander efficacy. Considering these findings, and the potential for some recreational sport atmospheres to create an increased risk of SV violence (e.g., loyalty to teammates, competitiveness), it is important to treat recreational athletes as a distinct campus subgroup.…”
Section: Theoretical Frameworkmentioning
confidence: 75%
“…While intercollegiate athletes reported similar rates of experiencing SV as non-athletes, they were more likely to commit SV. Therefore, we would like to suggest SV prevention education is needed at all levels of college sport, including a targeted team-level focus (Evans et al, 2022), as well as education for coaches and athletic trainers (Raj et al, 2017). Effective violence prevention education is comprehensive with sufficient dosage, utilizes well-trained educators, is theory driven and socio-culturally relevant, and includes varied teaching methods (Nation et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations